Trajectories of the Expression of Negative Emotion from Kindergarten to First Grade: Associations with Academic Outcomes - Hernández, Maciel M. (J Educ Psychol, 2017)
We examined individual trajectories, across four time points, of children’s (N = 301) expression of negative emotion in classroom settings and whether these trajectories predicted their observed school engagement, teacher-reported academic skills, and passage comprehension assessed with a standardized measure in first grade. In latent growth curve analyses, negative expressivity declined from kindergarten to first grade with significant individual differences in trajectories. Negative expressivity in kindergarten inversely predicted first grade school engagement and teacher-reported academic skills, and the slope of negative expressivity from kindergarten to first grade inversely predicted school engagement (e.g., increasing negative expressivity was associated with lower school engagement). In addition, we examined if prior academic functioning in kindergarten moderated the association between negative expressivity (level in kindergarten and change over time) and academic functioning in first grade. The slope of negative expressivity was negatively associated with first grade school engagement and passage comprehension for children who had lower kindergarten school engagement and passage comprehension, respectively, but was unrelated for those with higher academic functioning in kindergarten. That is, for children who had lower kindergarten school engagement and passage comprehension, greater declines in negative expressivity were associated with higher first grade school engagement and passage comprehension, respectively. The findings suggest that negative emotional expressivity in school is associated with academic outcomes in first grade and, in some cases, this association is more pronounced for children who had lower kindergarten academic functioning.